PENGARUH LINGKUNGAN KERJA, KOMITMEN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMA NEGERI 1 GU KABUPATEN BUTON TENGAH - Alimin Alimin; Adnan Hakim; Nasrul Nasrul; Eliyanti Agus Mokodompit; Sabri Sabri (Pascasarjana Universitas Halu Oleo, 2021)
This study aims to explain and examine: (1) the effect of the work environment, organizational commitment, and work motivation on teacher performance, (2) the effect of the work environment on teacher performance, (3) the effect of organizational commitment on teacher performance, and (4) the effect of work motivation on teacher performance. This research approach is survey with explanatory research design. Data collection was carried out in a cross-sectional manner using an instrument in the form of a questionnaire. The population in this study were all 53 teachers of SMA Negeri 1 Gu. The sampling technique is a saturated sample (census) where the entire population is used as the research sample. Data analysis techniques to answer the research hypothesis are descriptive and multiple linear regression. The results showed that: (1) work environment, organizational commitment, and work motivation simultaneously had a significant effect on teacher performance, (2) work environment had a significant effect on teacher performance, (3) organizational commitment had a significant effect on teacher performance, (4) work motivation has a significant effect on teacher performance. Keywords: Work Environment, Organizational Commitment, Work Motivation Teacher Performance.